Prognostic value of lipid profile in adult hemophagocytic lymphohistiocytosis - Cheng, Wanying; Wang, Lingling; Gao, Xin; Duan, Limin; Shu, Yongqian; Qiu, Hongxia (Frontiers in Oncology, 2023)
Background: Secondary hemophagocytic lymphohistiocytosis (sHLH) is a rare clinical syndrome with a high mortality rate. Currently, there are no feasible prognostic factors to clinically predict untreated sHLH patients' prognosis. Our objective was to characterize the lipid profile of adult sHLH patients and to determine the relationship with overall survival. Methods: We retrospectively analyzed 247 patients with newly diagnosed sHLH from January 2017 to January 2022 according to the HLH-2004 criteria. Multivariate Cox regression analyses and restricted cubic splines were conducted to evaluate the prognostic value of the lipid profile. Results: The median age of all patients was 52 years, and the commonest cause of sHLH in our cohort was malignancy. During a median follow-up of 88 (interquartile ranges, 22–490) days, 154 deaths occurred. The univariate analysis confirmed total cholesterol (TC) ≤ 3 mmol/L, triglycerides (TG) > 3.08 mmol/L, high-density lipoprotein cholesterol (HDL-c) ≤ 0.52 mmol/L, and low-density lipoprotein cholesterol (LDL-c) ≤ 2.17 mmol/L were associated with an inferior survival. In a multivariate model, HDL-c, hemoglobin, platelet, fibrinogen, and soluble interleukin-2 receptor were considered as independent factors. Additionally, the restricted cubic spline analyses indicated an inverse linear association between HDL-c and the risk of mortality in sHLH. Conclusion: Lipid profiles, which were low-cost and readily available promising biomarkers, were strongly associated with the overall survival in adult sHLH patients.